Aortic arch plaque morphology in patients with coronary artery disease undergoing coronary computed tomography angiography with wide-volume scan. Issue 7 (22nd July 2022) - Otsuka, Kenichiro; Ishikawa, Hirotoshi; Kono, Yasushi; Oku, Shinya; Yamaura, Hiroki; Shirasawa, Kuniyuki; Hirata, Kumiko; Shimada, Kenei; Kasayuki, Noriaki; Fukuda, Daiju
Abstract : Background: Wide-volume scanning with 320-row multidetector computed tomography coronary angiography (CTCA-WVS) enables the assessment of the aortic arch plaque (AAP) morphology and coronary arteries without requiring additional contrast volume. This study aimed to investigate the prevalence of AAPs and their association with coronary artery disease (CAD) and major adverse cardiovascular events (MACEs) in patients who underwent CTCA-WVS. Methods: This study included 204 patients without known CAD (mean age, 65 years; 53% men) who underwent CTCA-WVS. We evaluated the presence of aortic plaques in the ascending aorta, aortic arch, and thoracic descending aorta using CTCA-WVS. Large aortic plaques were defined as plaques of at least 4 mm in thickness. A complex aortic plaque was defined as a plaque with ulceration or protrusion. MACEs were defined as composite events of cardiovascular (CV) death, nonfatal myocardial infarction, and ischemic stroke. Results: AAPs and large/complex AAPs were identified in 51% ( n = 105) and 18% ( n = 36) of the study patients, respectively. The prevalence of AAPs with large/complex morphology increased with CAD severity (2.1% in no CAD, 12% in nonobstructive CAD, and 39% in obstructive CAD). The univariate Cox hazard model demonstrated that the predictors associated with MACEs were diabetes, obstructive CAD, and large/complex AAPs. Independent factors associated with large/complex AAPs were male sex [odds ratio (OR), 2.90; P = 0.025], stroke history (OR, 3.48; P = 0.026), obstructive CAD (OR, 3.35; P = 0.011), and thoracic aortic calcification (OR, 1.77; P = 0.005). Conclusion: CTCA-WVS provides a comprehensive assessment of coronary atherosclerosis and thoracic aortic plaques in patients with CAD, which may improve the stratification of patients at risk for CV events.